BUSINESS DEVELOPMENT STRATEGY USING SWOT METHOD (Study On White Wood Oil Refining Ud. Tegal Arum) - Mita Rahmawati; Abid Muhtarom; Zulkifli Lubis (Sean Institute, 2023)
This study aims to determine the best marketing strategy that can be applied by UD Eucalyptus Oil Refinery. Tegal Arum in providing good quality, so that it can increase its sales and find out whether the right marketing strategy is by using a SWOT analysis at the UD Eucalyptus Oil Refinery. Tegal Arum. This research is a research with a qualitative approach with the type of case study research on the object using SWOT analysis, IFAS, EFAS, and SWOT matrix. From the results of the SWOT, IFAS, and EFAS analysis shows that the IFAS table shows a difference in score of -0.09 and the EFAS table shows a difference in score of 0.24 so that it is in quadrant III, which supports the turnaround strategy. Based on the above results, the marketing strategy using SWOT, IFAS, and EFAS at UD Eucalyptus Oil Refinery. Tegal Arum is already in quadrant III, which is supporting the turnaround strategy, which means UD Eucalyptus Oil Refining. Tegal Arum has enormous opportunities, but also has various internal constraints or weaknesses.